Silica uptake by Spartina—evidence of multiple modes of accumulation from salt marshes around the world - Carey, Joanna C.; Fulweiler, Robinson W. (Frontiers in Plant Science, 2014)
Silicon (Si) plays a critical role in plant functional ecology, protecting plants from multiple environmental stressors. While all terrestrial plants contain some Si, wetland grasses are frequently found to have the highest concentrations, although the mechanisms driving Si accumulation in wetland grasses remain in large part uncertain. For example, active Si accumulation is often assumed to be responsible for elevated Si concentrations found in wetland grasses. However, life stage and differences in Si availability in the surrounding environment also appear to be important variables controlling the Si concentrations of wetland grasses. Here we used original data from five North American salt marshes, as well as all known published literature values, to examine the primary drivers of Si accumulation in Spartina, a genus of prolific salt marsh grasses found worldwide. We found evidence of multiple modes of Si accumulation in Spartina, with passive accumulation observed in non-degraded marshes where Spartina was native, while rejective accumulation was found in regions where Spartina was invasive. Evidence of active accumulation was found in only one marsh where Spartina was native, but was also subjected to nutrient over-enrichment. We developed a conceptual model which hypothesizes that the mode of Si uptake by Spartina is dependent on local environmental factors and genetic origin, supporting the idea that plant species should be placed along a spectrum of Si accumulation. We hypothesize that Spartina exhibits previously unrecognized phenotypic plasticity with regard to Si accumulation, allowing these plants to respond to changes in marsh condition. These results provide new insight regarding how salt marsh ecosystems regulate Si exchange at the land-sea interface.